Complexos de inclusão com amilose: obtenção, caracterização e avaliação como sistemas de liberação controlada de fármacos - Carbinatto, Fernanda Mansano [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
High amylose, one modified starch with high content of amylose (70%) is a promising material for controlling the delivery of different drugs. The ability of the high amylose to form inclusion complexes with high enzymatic resistance was exploited for obtaining controlled drugs delivery systems for targeting the drug release in the intestine by digestion with pancreatin enzyme. Different complexes were produced and the influence of the ratio drug: polymer, temperature and the presence of palmitic acid were evaluated through the characterization of the complexes by DSC, X-ray diffraction, particle size distribution, NMR and liquid uptake analysis. The performance of these complexes as controlled drug delivery systems was evaluated by determining the in vitro release of nimesulide (NMS) and praziquantel (PZQ) in different media, simulating the different regions of the gastrointestinal (GI) tract. The methodology to obtain the complex has been successful with a yield over 57% and the content of drug complexation until 68.16%. The DSC, diffraction of X-rays and NMR data showed the interaction between drug and polymer as well as the formation of inclusion complexes with semi-crystalline structures which were related to the formation of type II complexes with high enzymatic resistance. The higher crystallinity and the presence of drugs near to the complexes surface promoted the reduction of liquid uptake ability. The inclusion of drugs in complex allowed the reduction of their rates of release in the acid media (pH 1.2) and phosphate buffer (pH 6.9). The addition of pancreatin enzyme caused a significant acceleration of the rate of release of drugs (NMS and PZQ) showing the degradability of these complexes. The higher crystallinity of PZQ1:30AG60°C complex showed its highest enzymatic resistance providing the release of PZQ during 240min, while the complexes with NMS and PZQ 1:5AG90°C complex released the drug in 60min. The release data in media...

A alta amilose, um amido modificado com alto teor de amilose (70%), que demonstrou em diversos estudos ser um material promissor para o controle da liberação de diferentes fármacos. A habilidade da alta amilose em formar complexos de inclusão e a elevada resistência enzimática foi explorada para a obtenção de sistemas de liberação controlada de fármacos com intuito vetorizar a liberação do fármaco no intestino, através da digestão pela enzima pancreatina. Diferentes complexos foram produzidos e a influencia da proporção fármaco: polímero, temperatura, e a presença de ácido palmítico foram avaliados através da caracterização dos complexos pelas análises de DSC, difração de Raios-X, distribuição granulométrica, RMN e determinação da capacidade de absorção de líquido. O desempenho como sistemas de liberação controlada de fármacos foi avaliado através da determinação da liberação in vitro dos fármacos nimesulida (NMS) e praziquantel (PZQ) em diferentes meios, simulando as diferentes regiões do trato gastrintestinal (TGI). A metodologia para a obtenção dos complexos mostrou-se eficiente com rendimento superior a 57% e teor de fármaco complexado de até 68,16%. Os dados de DSC, difração de Raios-X e RMN relevaram a interação entre fármaco e polímero, bem como a formação dos complexos de inclusão com estruturas semi-cristalinas associadas a formação de complexos do tipo II, de elevada resistência enzimática. A maior cristalinidade e a presença de fármacos próximos à superfície dos complexos promoveram redução da capacidade de absorção de líquido. A inclusão dos fármacos nos complexos permitiu a redução de suas taxas de liberação nos meios sem enzima (ácido, pH 1,2 e tampão fosfato pH 6,9). A adição da enzima pancreatina promoveu significativa aceleração das taxas de liberação dos fármacos (NMS e PZQ) demostrando a degradabilidade desses complexos. A maior ...
Keywords: Fármacos; Farmacologia; Polimeros; Polymers